Modelling and simulation of side milling using finite element analysis - Wong, Choon Fuan (2016)
This project deals with modelling and simulation of side milling using Finite Element Analysis. The objective of this thesis is to validate the cutting force result between simulation and experiment.It describes how the finite element analysis predicts the cutting force before the machining process is proceeded. The data obtained in this project were cutting force and stress during the side milling process. Machining parameters such as cutting speed, feed rate, spindle speed were also studied. The cutting force and stress prediction was done by using finite element analysis software called ABAQUS. The finite element analysis was analyzed based on the interaction between aluminium 6061 work piece and high speed steel tool cutter. The cutting forces were measured by using dynamometer during the side milling process. The machining parameters were calculated before the experiment started. Finally, the cutting force in the three directions which is X, Y and Z direction versus time was measured and recorded in the data acquisition software which is Dyno-ware. From the results of dynamometer, noise has been eliminated to get the certain time period of cutting force. The results between simulation and experiment indicates that the predicted and the measured cutting force of milling process are in a good agreement.